2019
DOI: 10.1159/000504046
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Regional Variation in Clinical Practice on Thyroid Cancer Diagnosis: A National Population-Based Study

Abstract: Objective: Regional variation in thyroid cancer incidence in Belgium, most pronounced for low risk cancer, was previously shown to be related to variation in clinical practice, with higher thyroid surgery rates and lower proportions of preoperative fine-needle aspiration (FNA) in regions with high thyroid cancer incidence (period 2004–2006). The objective of this study was to investigate regional thyroid cancer incidence variation in relation with variation in thyroid surgery threshold in a more recent Belgian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…It is also worth noting that only 37% of DTC patients in this study had pre-surgical FNA use, which is higher than the estimate of 32% observed in the US [ 42 ], but lower than the estimate of 41-73% across different regions of Belgium [ 43 ]. Although ATA and other Associations recommend FNA as an important preoperative diagnostic tool for thyroid nodules, it is not widely accepted in China, and some hospitals use intraoperative frozen section for diagnosis.…”
Section: Discussioncontrasting
confidence: 66%
“…It is also worth noting that only 37% of DTC patients in this study had pre-surgical FNA use, which is higher than the estimate of 32% observed in the US [ 42 ], but lower than the estimate of 41-73% across different regions of Belgium [ 43 ]. Although ATA and other Associations recommend FNA as an important preoperative diagnostic tool for thyroid nodules, it is not widely accepted in China, and some hospitals use intraoperative frozen section for diagnosis.…”
Section: Discussioncontrasting
confidence: 66%
“…In the Netherlands a restrictive diagnostic work-up strategy is standard care for thyroid nodules, recommending diagnostic work-up only for palpable nodules, preventing fine needle aspiration (FNA) biopsies of incidentalomas detected by imaging [ 8 ]. Since 2013, the number of PET/CT scans performed grew by 6% annually, and together with the exponential increase in use of US imaging, more incidentalomas are found [ 10 , 11 , 14 ]. However, the Dutch guideline only recommend diagnostic FNA for patients with palpable or symptomatic thyroid nodules, which possibly prevents a significant amount of indolent PTC from being diagnosed, resulting in more intensely selected and possibly more aggressive recorded PTCs in The Netherlands when compared to the U.S. population [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to the ATA guidelines, the Dutch guidelines recommend more restricted work-up for thyroid incidentalomas recommending only fine needle aspiration (FNA) in case of a ‘palpable thyroid nodule’. [ 8 , 9 ] Multiple studies showed that increased use of imaging modalities leads to increased number of PTC diagnoses, mostly without clinical relevance [ 10 , 11 ]. Subsequently, using a restrictive diagnostic work-up algorithm may result in the identification of less PTCs with an indolent nature and may lead to a patient population with relatively more aggressive PTCs.…”
Section: Introductionmentioning
confidence: 99%
“…Although relevant medical experts have formulated relevant rules for the diagnosis and treatment of thyroid cancer [9], the relevant regulations for the implementation of medical insurance do not specifically consider the actual clinical situation. It is still difficult to avoid the occurrence of over-diagnosis and over-treatment in clinical practice [10]. Under this situation, the medical cost of thyroid cancer treatment is not covered by the medical insurance reasonably according to the clinical diagnosis and treatment [11].…”
Section: Discussionmentioning
confidence: 99%